Capacity building to NARES and private sector in RiceAdvice Lite deployment and validation in irrigated and rainfed lowlands in Mali - Ahouanton, K.; Dossou-Yovo, E.R. (2024)
This report presents the activities and outcomes of the training in RiceAdvice Lite validation trial (RAL VAT) conducted under the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project to the staff of the Institute for Rural Economics and the Syngenta Foundation for Sustainable Agriculture. In total, 30 staff from IER and Syngenta Foundation including 28 males, and 2 females were trained in May 2024 and provided with backstopping to support 100 farmers in the implementation of the recommendations from May to June 2024. The training aimed to equip participants with skills to generate site-specific fertilizer recommendations using RiceAdvice Lite, set up rice trial plots and collect data to monitor use of chemical fertilizer, rice yield, farmers income, and nutrient use efficiency. The demonstration trials occurred in 100 farmers’ fields equally distributed in rainfed and irrigated systems of the regions of Sikasso and Segou. Next steps include monitoring the trials during critical stages, ensuring the accurate application of the protocol, and supporting data collection to validate the RiceAdvice Lite tool for scaling up in Mali.